Territorial behaviour of wild Shovelers at Delta, Manitoba - Seymour, Norman R (Wildfowl, 1974)
The territorial behaviour of wild Shovelers Anas clypeata was studied on a 1.9-km long roadside ditch at Delta, Manitoba, Canada. Most of the data used was derived from observations of seventeen marked males and three marked females. Breeding activity on the study area spanned 12 weeks and twelve different territorial pairs were observed. Breeding activity ceased late in the season partly as a consequence of widespread nest predation. Aggressive behaviour of territorial males took several forms and contributed to the establishment and maintenance of territories. Such behaviour occurred primarily within 30 m of the focal loafing spot and was not noted further away than 90 m. Boundaries were well defined only where there were frequent interactions. Defence was primarily of the water area and not the adjacent meadows. There was a vertical component to the territory. The area used by pairs became significantly smaller (0.9 ha) after the onset of egg-laying. Territory size did not significantly change later in the season despite an increased concentration of pairs. Territories were remarkably stable and no pairs lost territories as a result of hostility. However, stability may break down when the pair-bond weakens with advance of incubation or when the nest is destroyed. Certain areas were occupied by as many as three successive pairs. Pairs spent virtually all their time on the territory after egg-laying was well advanced. Females still used the territory after dissolution of the pair-bond although their activities were restricted to the area around the loafing spot.